2020
DOI: 10.1038/s41598-020-62183-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community profiling of ammonia and nitrite oxidizing bacterial enrichments from brackishwater ecosystems for mitigating nitrogen species

Abstract: Nitrogen species such as ammonia and nitrite are considered as major stressors in modern aquaculture practices. We developed enrichments of ammonia oxidising bacteria (AOB) and nitrite oxidising bacteria (NOB) for effective mitigation of nitrogenous wastes in the shrimp culture operations. The objective of this study was to understand the microbial community composition of AoB and noB enrichments using the V3-V4 region of the 16S rDNA gene by Illumina MiSeq sequencing. The analysis revealed 2948 and 1069 OTUs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 63 publications
(59 reference statements)
1
36
0
Order By: Relevance
“…In the same study, as well as in a study by Keeley et al (2018) , also Thermodesulfovibrionaceae, which can utilize nitrate, sulfite, thiosulfate, and sulfate as terminal electron acceptors, were characterized as indicative of far-field, unenriched sites. Thermodesulfovibrionaceae and Nitrospiraceae often co-occur in benthic marine nitrogen-metabolizing communities ( Baskaran et al, 2020 ). Likewise, Ectothiorhodospiraceae include widely distributed aerobic and anaerobic bacteria capable of nitrite and sulfur oxidation ( Oren, 2014 ), which were previously reported as indicators of high-to-good environmental quality in coastal sediments ( Aylagas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, as well as in a study by Keeley et al (2018) , also Thermodesulfovibrionaceae, which can utilize nitrate, sulfite, thiosulfate, and sulfate as terminal electron acceptors, were characterized as indicative of far-field, unenriched sites. Thermodesulfovibrionaceae and Nitrospiraceae often co-occur in benthic marine nitrogen-metabolizing communities ( Baskaran et al, 2020 ). Likewise, Ectothiorhodospiraceae include widely distributed aerobic and anaerobic bacteria capable of nitrite and sulfur oxidation ( Oren, 2014 ), which were previously reported as indicators of high-to-good environmental quality in coastal sediments ( Aylagas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrifying bacteria along with lactobacillus is one of the best probiotic for enhancing fish production and maintenance of water quality parameters like temperature, DO, pH, ammonia, nitrite and nitrate (Karthik et al 2016). Small scale experiments in different aquaculture farms using nitrifying bacteria as probiotics to promote the water quality and reduction in load of pathogenic bacteria were conducted (Padmavathi et al 2012;Barik et al 2018;Baskaran et al 2020). Consequently, nitrifying bacteria can be used extensively as water probiotics in aquaculture for bioremediation.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed the presence of microbial groups involved in nitrification, denitrification and establishing a microcosm with dissimilatory nitrate reduction to ammonium (DNRA) and assimilatory nitrate reduction in addition to ammonia‐ and nitrite‐oxidizing autotrophs (Baskaran et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment developed from brackishwater environment (18–35‰) performs efficiently in brackishwater aquaculture (Baskaran et al . 2020), whereas low saline (LS) aquaculture needs microbes enriched from LS environments, which can perform well. The present study aims to understand the abundance and diversity of nitrifying bacteria in the enrichments developed from LS environments in comparison with brackishwater environments.…”
Section: Introductionmentioning
confidence: 99%